Teacher-student relationship quality: Teachers' theories of actions in Egyptian schools - Eid, Lamiaa Mohamed Fathy (AUC Knowledge Fountain, 2020)
A robust body of research has focused on the significance of teacher-student relationship quality (TSRQ) and how it plays a substantial role in the trajectory of students’ development, where teachers are typically seen as the main actor in improving this relationship. Nonetheless, minimal research attention has been directed towards exploring teachers’ perceptions of TSRQ. Accordingly, this qualitative study was carried out to explore teachers’ perceptions concerning the quality of TSR, who work at two schools affiliated to the School-University Partnership for Peer Communities of Learners project. The study adopted Argyris and Schon’s theories of actions as its theoretical framework to examine the degree of congruence between the theories-in-use and espoused theories of 13 teachers to discover their actual perceptions. It further was informed by the attachment and self-determination theories when describing teachers’ behavioral interactions with students. This study followed the micro-ethnographic design that entailed the researcher’s full involvement in the participants’ natural environment. Data were gathered, at two phases, via using three methods of interviewing, analyzing documents, and participant observation while adopting a covert role to avoid the artificial responses typical of controlled conditions. The study used thematic analysis to extract TSR themes and to find any instances of internal inconsistency. It further utilized constant comparative analysis to explore the degree of congruency between teachers’ theories-in-use and espoused theories. Findings revealed that the significant majority of teachers’ five espoused themes were internally consistent. Also, their level of congruity was differentiated along a continuum, where nearly half of the sampling acted 100 % congruent with their espoused theories. The study found that empowerment appeared to be the impetus for teachers’ motivated behavior in transforming their TSR. Their practices became aligned to the principles of the Convention on the Rights of the Child (international human rights treaty). The findings provided a more in-depth insight into the impact of reflection and congruent theories of actions of TSRQ on having a healthy environment for learning for both teachers and students.